Aaja Nach Lai [Come Dance]: Performing and Practicing Identity among Punjabis in Canada - Mooney, Nicola (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2008)
AbstractThis article discusses the performance of Punjabi folk dances bhangra and giddha in some Canadian contexts. After introducing a notion of Punjabi identity, the article provides a brief description of these dance forms, their agrarian origins and their gendered natures, as well as of the types of events at which these dances are performed among Canadian Punjabis, and specifically, Jat Sikhs. I argue that not only do these dances express and maintain Punjabi identity in diasporic contexts, but that these identities refer to a Jat “rural imaginary” that is actively constructed through dance and music in response to the displacement of urban and transnational migration. This rural imaginary is usurped by bhangra’s increasing Westernization and popularity in the non-Jat South Asian diaspora, thus raising challenges to Jat centrality, meaning, and identity.